On improvement in representation of foE in IRI. Issue 2 (15th July 2017) - Yang, Zhe; Ssessanga, Nicholas; Tran, Lan Thi; Bilitza, Dieter; Kenpankho, Prasert
Highlights: Improve foE representation in IRI. IRI is driven using daily F10.7 and F10.7_81 indices. Results are compared to ionosonde measurements at low, mid and high latitudes. F10.7_81 index performs better than daily F10.7 index. Abstract: Improvements in representation of foE for use in the International Reference Ionosphere (IRI) model are investigated. The IRI model currently depends on the 12-month running mean of sunspot number to estimate the foE. Using the F10.7 daily and F10.7_81 indices as the new model drivers, results are compared to ionosonde measurements at low, mid and high latitudes during solar minimum and solar maximum. Results show that the IRI model estimates the foE parameter better at low-mid latitudes than at high latitudes, specifically during solar maximum. Using the F10.7 indices to derive the IRI model improves estimates of foE, specifically at low-mid latitudes. The F10.7_81 index was found to perform better than the daily F10.7 index. Improvements during solar maximum and during solar minimum were on average 3.5% and 1%, respectively. Therefore, the F10.7_81 index is recommended as IRI model driver for foE estimates.